2013
DOI: 10.1515/ijamh-2013-0057
|View full text |Cite
|
Sign up to set email alerts
|

Attention deficit hyperactivity disorder and dual disorders. Educational needs for an underdiagnosed condition

Abstract: A wide range of comorbid psychiatric disorders overlap with attention-deficit hyperactivity disorder (ADHD) across the life span. There is a robust and complex link between ADHD and substance use disorders (SUD). The aim of this report was to review the neurobiological and other vulnerability factors explaining the comorbidity of ADHD and an addictive disorder, as well as the key aspects of the assessment and diagnosis of dually diagnosed ADHD patients. A comprehensive and systematic search of relevant databas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 94 publications
0
20
0
Order By: Relevance
“…The National Comorbidity Survey reported that adults with ADHD are three times more likely to develop major depressive disorder (MDD), six times more likely to develop dysthymia, and more than four times more likely to have any mood disorder [ 37 ]. Most notably, individuals with ADHD are twice as likely to experience substance abuse or dependence [ 43 ]. These comorbidities present important clinical challenges since their co-occurrence results in greater disease burden and more severe illness courses than ADHD or mood and anxiety disorders alone [ 44 ].…”
Section: Main Textmentioning
confidence: 99%
See 1 more Smart Citation
“…The National Comorbidity Survey reported that adults with ADHD are three times more likely to develop major depressive disorder (MDD), six times more likely to develop dysthymia, and more than four times more likely to have any mood disorder [ 37 ]. Most notably, individuals with ADHD are twice as likely to experience substance abuse or dependence [ 43 ]. These comorbidities present important clinical challenges since their co-occurrence results in greater disease burden and more severe illness courses than ADHD or mood and anxiety disorders alone [ 44 ].…”
Section: Main Textmentioning
confidence: 99%
“…Studies have concluded that emotional dysregulation is a distinctive attribute of adult ADHD psychopathology, however these symptoms may be misdiagnosed as a mood disorder [ 66 68 ]. Similarly, ADHD symptoms may be masked by substance use [ 43 ]. Physicians are often more familiar with mood and anxiety disorders, which may contribute to misdiagnosis and delays in treating ADHD in adults [ 69 ].…”
Section: Main Textmentioning
confidence: 99%
“…The literature argues towards a targeted training on the dual-diagnosis of ADHD and SUD [20]. The expert group recommends that a physician or clinical psychologist can make the diagnosis of ADHD in SUD patients, provided he/she has received extensive training on the differential diagnosis of ADHD, has experience in addiction care, and has experience with adult ADHD populations.…”
Section: Consensus Statement For the Screening And Diagnosis Of Adhd mentioning
confidence: 99%
“…Whilst some of the children described by Still, as is probably the case of some the earlier descriptions included in the present report, may have suffered from a variety of neurological and psychiatric disorders, including conduct disorder, oppositional defiant disorder, learning disabilities, autism spectrum disorders, epilepsy, chorea, among many others, many of these children showed clear symptoms of ADHD and may present with these comorbid disorders, as it is commonly the case in clinical practice. Moreover, as we now fully comprehend, the existence of other comorbid disorders not only does not exclude a diagnosis of ADHD, but often makes the diagnostic process of this neurodevelopmental disorder more difficult [74] . In any case, although many of the symptoms and diagnostic criteria of inattention, hyperactivity and impulsivity are not exclusive to this neurodevelopmental disorder, the characteristic presentation of these symptoms, are typical of the disorder currently known as ADHD, as indicated not only in the solid neurobiological research on this disorder, but on the broad and diverse clinical descriptions published during the 20 th century and, as outlined in the present report, in the various medical descriptions during the 18 th and 19 th centuries.…”
Section: Resultsmentioning
confidence: 99%